Impact of anesthetic technique on troponin I levels in pediatric cardiac surgery: a randomized clinical trial - João Victor Galvão Barelli; David D. Araujo; Suely P. Zeferino; Gustavo M. Dantas; Filomena B. Galas (Brazilian Journal of Anesthesiology)
Background: This study aimed to evaluate the effects of the inhalational anesthetic sevoflurane on postoperative myocardial injury and renal function in children under 2 years old with congenital heart disease (RACHS 1, 2, and 3) undergoing cardiac surgery with extracorporeal circulation. Methods: A randomized clinical trial was conducted with 66 patients divided into two groups: one receiving sevoflurane and the other Total Intravenous Anesthesia (TIVA). The primary outcome was the serum troponin I levels within the first 48 hours postoperatively. Secondary outcomes included urine output and serum urea levels. Results: The median troponin I levels at 48 hours were 10.5 ng.mL−1 (IQR: 8.2–12.7) in the sevoflurane group and 11.0 ng.mL−1 (IQR: 8.7–13.0) in the TIVA group (p = 0.336). The sevoflurane group showed higher urine output on the second postoperative day (median: 800 mL [IQR: 420–913] vs. 541 mL [IQR: 312–718], p = 0.034) and lower serum urea levels (median: 24 mg.dL−1 [IQR: 16–35] vs. 36 mg.dL−1 [IQR: 23–49], p = 0.030). Conclusions: While sevoflurane did not significantly impact myocardial injury markers, it demonstrated potential renal protective effects in this patient population. Further research is necessary to confirm these findings across different pediatric age groups and surgical contexts.